The Compendium of Spanish Numismatic Ancient (1849) by José de Viú. Notes for Spanish numismatic historiography on XIX century - Conejo Delgado, Noé (Revista General de Información y Documentación, 2015)
In this paper, we make a constructive criticism about one unpublished numismatics book of José de Viú. We will provide a context for this book, and we will connect its contents with other contemporary authors. With this work, we hope to contribute one new reading about the development of Spanish numismatic ancient in the XIX century.